18β-Glycyrrhetinic acid protects against alpha-naphthylisothiocyanate-induced cholestasis through activation of the Sirt1/FXR signaling pathway. (December 2018) - Wu, Shou-yan; Cui, Shi-chao; Wang, Le; Zhang, Yi-ting; Yan, Xiao-xia; Lu, Heng-lei; Xing, Guo-zhen; Ren, Jin; Gong, Li-kun
Abstract Cholestasis is a common feature of liver injury, which manifests as bile acid excretion and/or enterohepatic circulation disorders. However, very few effective therapies exist for cholestasis. Recently, 18β-Glycyrrhetinic acid (18b-GA), a major metabolic component of glycyrrhizin, which is the main ingredient of licorice, was reported to protect against alpha-naphthylisothiocyanate (ANIT)-induced cholestasis. However, its protective mechanism remains unclear. We hypothesized that 18b-GA may stimulate the signaling pathway of bile acid (BA) transportation in hepatocytes, resulting its hepatoprotective effect. According to the results, 18b-GA markedly attenuated ANIT-induced liver injury as indicated the hepatic plasma chemistry index and histopathology examination. In addition, the expression levels of nuclear factors, including Sirt1, FXR and Nrf2, and their target efflux transporters in the liver, which mainly mediate bile acid homeostasis in hepatocytes, significantly increased. Furthermore, we first revealed that 18b-GA treatment significantly activated FXR, and which can be significantly reduced by EX-527 (a potent and selective Sirt1 inhibitor), indicating that 18b-GA activates FXR through Sirt1. Taken together, 18b-GA confers hepatoprotection against ANIT-induced cholestasis by activating FXR through Sirt1, which promotes gene expression of the efflux transporter, and consequently attenuates dysregulation of bile acid homeostasis in hepatocyte compartments.